Forensic Science in Criminalistics in Indonesia: Development and Challenges - Istri Wulandari (Unnes Law Journal, 2023)
Since the birth of forensic science until now it has developed so rapidly. the division of forensic science is so complete that it is able to assist law enforcement in carrying out the task of disclosing criminal cases. The application of forensic science has also undergone standardization that is recognized by the international community, so that in future trials, the use of forensic science can be clearly accounted for. The use of forensic science in Indonesia is the same as following international standards using standards set by the National Accreditation Agency. So that in the end it is professional staff who are needed to manpower the needs of the use of forensic science, at least being able to prevent the perpetrators of crimes from continuing their crimes.